Introduction to queueing systems with telecommunication applications - Lakatos, Laszlo; Szeidl, Laszlo; Telek, Miklos (New York : Springer, 2013)
Opening with an introduction to probability theory and stochastic processes, this book shows how phase type distributions, Markov arrival processes and quasi-birth death processes apply in queuing models and their applications. Includes examples and exercises.
1. Introduction to probability theory -- 2. Introduction to stochastic processes -- Markov chains -- Renewal and regenerative processes -- Markov chains with special structures -- 6. Introduction to queueing systems -- 7. Markovian queueing systems. -- 8. Non-Markovian queueing systems -- 9. Queueing systems with structured Markov chains. -- 10. Queueing networks -- 11. Applied Queueing Systems
Includes bibliography and index.
Keywords: Mathematics; Special Topics; Queuing theory; Telecommunication systems; Mathematical models